Exploring EFL Students’ Attitudes of Artificial Intelligence (AI) as a Tool for Writing English Thesis Proposals in Higher Education - Winarti, Hesti; Kholid, M. Ridho; Zakiyah, Zakiyah (Jayapangus Press, 2025)
This study explores EFL students' attitudes towards the use of Artificial Intelligence (AI) in writing English thesis proposals in higher education. The rapid advancement of AI technology has encouraged many university students to use AI-based tools to improve the quality of their academic writing. Using a descriptive qualitative approach, this study examined students' perceptions, experiences, and challenges. Data were collected through a questionnaire involving 35 English Education students at UIN Raden Intan Lampung as well as semi-structured interviews with 10 selected participants. The results showed that most students had a positive attitude towards AI due to its ability to improve writing efficiency, grammatical accuracy, and text organization. AI also helps in generating ideas, structuring arguments, and providing quick feedback, thus reducing anxiety in writing. However, there are concerns about over-reliance on AI that may stifle critical thinking and creativity. In addition, students were aware of the ethical challenges of using AI, especially regarding originality and the risk of plagiarism. Some students also customized AI results to better suit academic standards, which show that they did not fully rely on AI without re-evaluating. This study concludes that AI can be an effective support tool in thesis proposal writing if used wisely. Therefore, this study emphasizes the need for AI literacy in higher education to help students understand the limitations and ethical implications of its use. With the right approach, AI can be an effective support tool in developing students' academic abilities.